PREDICTION OF FINANCIAL DISTRESS USING THE ALTMAN AND ZMIJEWSKI MODELS - Regita Puji Cahyani; Dewa Gede Wirama (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the prediction of financial distress in all non-financial firms listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023 using the Altman Z-Score Model and the Zmijewski Model, as well as to compare the prediction accuracy levels of both models. Financial distress is a condition in which a firm experiences financial difficulties that may lead to bankruptcy. This study employs a quantitative approach with a descriptive method. The research sample consists of 250 firms determined by stratified random sampling and analyzed using the non-parametric Mann-Whitney test and prediction accuracy testing through the Bootstrapping method. The results show that there is a significant difference between the Altman Model and the Zmijewski Model in predicting financial distress. Furthermore, the Zmijewski Model shows a higher prediction accuracy of 95.1% compared to the Altman Model at 89.6%. These findings are expected to provide theoretical and practical contributions, particularly for decision-making by firm management, investors, and creditors.